Nosocomial spread of Mycobacterium bovis in domestic cats. Issue 2 (February 2015) - Murray, Aisling; Dineen, Andrea; Kelly, Pamela; McGoey, Karen; Madigan, Gillian; NiGhallchoir, Eadaoin; Gunn-Moore, Danièlle A
Five domestic cats were euthanased owing to confirmed or suspected Mycobacterium bovis infection. The initial source of infection remains unclear. Cat A was presented to a veterinary clinic in County Kildare, Ireland, with a discharging submandibular lesion. The infection appears to have been transmitted to four other cats through direct (cats B and C living in the same household as cat A) and non-direct (nosocomial spread during routine operations; cats D and E) contact over a 13.5-week period. Of the five cases, two (B and D) had post-mortem examinations in which gross changes consistent with tuberculosis were seen, moderate numbers of acid-fast bacteria (AFB) were seen on microscopy and M bovis (spoligotype SB0978) was confirmed on culture. Of the remaining three cats, one had a swab taken from its draining ovariohysterectomy wound, which revealed large numbers of AFB with morphology consistent with M bovis (cat E). Two cases were euthanased without diagnostic tests; however, their history and clinical presentations were highly suggestive of tuberculosis (cats A and C). To our knowledge, this is the first documented case of nosocomial spread of M bovis in cats.